Public service recruitment in the Sudan - Al-Teraifi, Al-Agab A. (Philippine Journal of Public Administration, 1978)
The recruitment policies and practices in the Sudanese civil service suffer from several weaknesses such as: (1) lack of long-range recruitment policy in all government agencies, (2) absence of uniform methods of recruitment, (3) failure of the civil service leadership to understand the importance of the probationary period, and (4)preference of men over women in employment. Also, the socio-cultural and political environment has a great influence on recruitment policies and practices. Thus, although some public officials do adhere to modern bureaucratic norms and practices, many more seem to yield to personalism as a criterion in personnel selection and appointment. To eliminate or at least to minimize these deficiencies, the Public Service Recruitment Board was set up in 1974. However, although the reformed recruitment system is an improvement over the previous setup, it still has its weaknesses and limitations.